Auger-spectroscopy in quantum Hall edge channels and the missing energy problem - T. Krähenmann (Nature Portfolio, 2019)
Energy relaxation crucially impacts transport properties of mesoscopic devices. Here the authors show that energy can be distributed between distant parts of the sample, which may provide a resolution to an outstanding puzzle concerning energy conservation in transport through quantum Hall edges.